Is being muslim fact or a challenge? : a perspective on muslim identity, citizenship and Islamic education - Kazmi, Yedullah; Hashim, Rosnani (Palgrave Macmillan, 2010)
Like most religious communities Muslinls do not constitute a monolithic, undiftl'rcntiatcd community but display a rich variety of differences. This fact is not appreciated by Muslims and non-Muslims alike. Needless to say, this fact is hardly ever acknowledged in the discourse of Muslim education. This essay explores ways that this absence can be filled. Hence the challenge for Muslim educators is twofold: to design a learning and teaching situation that not only tolerates, but celebrates difference without surrendering commonality, and to imbue l\Iluslims with sufficiently robust historical consciousness to be effective historical actors. If educators meet this challenge successfully then the issue of citizenship can also easily be resolved